Exploring factors that impact activity participation of children and adolescents with severe developmental disabilities. Issue 12 (20th November 2017) - Taheri, A.; Perry, A.; Minnes, P.
Summary: Background: Despite the benefits of social participation, children and adolescents with developmental disabilities (DD) are often excluded from taking part in social activities. There is a gap in the literature about the factors that contribute to adequate participation of children with severe DD in particular and the barriers to their participation. Taking an ecological perspective, the purpose of this study was to examine child, family and community variables that may impact the activity participation of children and adolescents with severe DD. Methods: A total of 197 parents of children with severe DD (4–19 years) completed a survey, addressing a wide range of child, family and community related variables, as well as a measure of activity participation. Results: Overall, the final model significantly accounted for 30% of the variance in activity participation. Higher adaptive behaviour, greater parental socialisation and placement in an integrated school programme were significant predictors of greater activity participation. Conclusion: Child, family and community factors were all important in understanding the activity participation of children with severe DD, thus supporting the value of an ecological approach. Suggestions for future research and clinical implications are discussed.